THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TRAINING OF SPECIALISTS OF PHYSICAL EDUCATION AND SPORT - Volcu Gheorghe; Volcu Irina (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
The infiltration of information and communication technologies in the teaching-learning-evaluation process has become an intense topic addressed by the academic society and closely related to the modernization of education. Thus, the use of information and communication technologies is a necessary trend for the evolution of the field of physical education and sport, as well as for the training of the profile specialists.The process of globalization and the transition to a post-industrial society, focused on information technologies and knowledge, it emphasizes the need of new educational standards of professional training, focused on competences, as tools of realization of educational policies.